Studi Komparatif Onomatope Benda Mati Bahasa Jepang dan Bahasa Jawa - Santoso, Teguh; Gauhar Auliawan, Althaf (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2023)
This research is entitled ‘‘Comparative Study of Inanimate Onomatopoeic Studies in Japanese and Javanese Language’’. This study uses a qualitative method with a reference to a comparative study approach. The data used in this study came from various mixed data, including the novel Emas Sumawur, Panjebar Spirit magazine and the Japanese Yonkoma comic. The data collection in this study used a descriptive approach. The descriptive research method used is the study of Sudaryanto Onomatopoeia in Japanese is divided into two types, namely: giongo (words that imitate the sound of living things or sounds that come out of inanimate objects) and gitaigo (words that directly describe the state of sound). In Javanese, onomatopoeia are words that are formed based on imitation of sounds in the natural surroundings and sounds of certain inanimate objects. In this study, because the number of Japanese onomatopoeia is the highest compared to Javanese, this onomatopoeic research is only limited to words based on imitation of sounds on inanimate objects. In this study, the description of the comparative study used the study of Tarigan, while the onomatopoeic description of inanimate objects used the study of Akimoto (2002) and Mulyani This study aims to obtain a description of the differences or similarities of onomatopoeic inanimate objects in Japanese and Javanese based on data findings. The results of the research on inanimate objects in Japanese and Javanese, there are 16 data to find out how the differences or similarities of the onomatopoeia are.